Contrast training generates post-activation potentiation and improves repeated sprint ability in elite ice hockey players - Lagrange, S.; Ferland, P.-M.; Leone, M.; Comtois, A. S. (International Journal of Exercise Science, 2020)
The purpose of this study was to measure the generating effects of Contrast Training (CT) on 6-hour post-activation potentiation (PAP) and its influence on jumping and on on-ice repeated sprint performance in ice hockey players. Forty-one participants were divided in two groups: experimental (EG) and control group (CG). The EG followed the CT PAP protocol which consisted of 5 sets of 5 half inertia back squatsuperset with 6 squat jumps. The effects of PAP were measured with the vertical countermovement jump (CMJ), stationary broad jump (BJ) and 9 repeated on ice 40-meter maximal sprints with hockey equipment. Results showed that the PAP generated by the CT protocol had no significant impact (p=0.05) on CMJ, BJ, blood lactate concentration, heart rate peak and rated perceived exertion as EG and CG group presented no significant differences in improvement. However, results show that there was a significant improvement (p<0.05) for the EG in the total sprint time (-5.5±2.6%; 56.2±4.7 to 53.1±3.9sec) mean sprint speed (+5.9±3.0%; 6.4±0.5 to 6.8±0.5m/s) and in 1stsprint speed (+7.4%±5.9; 7.3±0.7 to 7.8±0.6m/s), but not for the CG (-1.4±5.1%; 58.0±5.4 to 57.2±6.4sec), (+1.7±5.1 %; 6.3±0.6 to 6.4±0.6m/s) and (+1.9±7.7%; 6.9±0.7 to 7.0±0.7m/s) respectively. Thus, results show that the CT protocol utilized in this study generated PAP which had an acute effect on the on-ice hockey repeated sprint test performance. Therefore, CT could be utilized punctually to improve repeated sprint performance of elite hockey players as it could potentially help create odd man rushes during games.KEY WORDS: Resistance training, complex training, skating speed, plyometric, rate of force development